1999
DOI: 10.1016/s0893-133x(99)00016-0
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Function is Differentially Altered in the Basal Ganglia of Chronic Schizophrenics

Abstract: In the present study, we have applied a novel strategy involving the postmortem measurement of the mitochondrial respiratory chain enzyme cytochrome-c oxidase (COX; complex IV) to identify regional changes in energy metabolism in the basal ganglia of chronic, medicated schizophrenics. COX activity was decreased in the caudate nucleus but increased in the putamen and nucleus accumbens. An increase in succinate dehydrogenase (complex II) was evident in the putamen and nucleus accumbens, but changes were not seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 38 publications
5
69
0
2
Order By: Relevance
“…[31][32][33][85][86][87][88] The results of this study extend this abnormality to bipolar disorder, whereby almost half of all significantly differentially expressed proteins identified were found to have a mitochondrial or other metabolic function. In the schizophrenia group, this figure was a quarter, suggesting that metabolic dysfunction in this area is relatively more prominent in bipolar disorder than schizophrenia.…”
Section: Discussionsupporting
confidence: 59%
“…[31][32][33][85][86][87][88] The results of this study extend this abnormality to bipolar disorder, whereby almost half of all significantly differentially expressed proteins identified were found to have a mitochondrial or other metabolic function. In the schizophrenia group, this figure was a quarter, suggesting that metabolic dysfunction in this area is relatively more prominent in bipolar disorder than schizophrenia.…”
Section: Discussionsupporting
confidence: 59%
“…These findings may highlight region-specific molecular mechanisms involved in the etiology of LH. In human studies, decreased mitochondrial function was demonstrated in the basal ganglia of chronic schizophrenics, 47,48 and inhibition of mitochondrial respiratory complex I activity was reported as a cellular pathology of Parkinson's disease. 49,50 Evidence, including that of decreased ATP in frontal lobes detected in depressive patients, 51 has generated speculation about the role of mitochondrial dysfunction in depression.…”
Section: Po005 (Lh-s Vs Lh-i) By Mann-whitney Test (Two-tailed)mentioning
confidence: 99%
“…The etiology of schizophrenia is still unknown but recent advances in neuroscience have suggested a wide array of competing mechanisms that may be involved in the disorder, [3][4][5][6] among them altered cerebral energy metabolism 7 and mitochondria dysfunction. [8][9][10][11][12][13][14] Recently, we have shown that platelet mitochondrial complex I, which is the first complex of the mitochondrial electron transport system, is significantly increased in schizophrenic patients in the acute state, and not in patients with affective disorders. 15 In the present study we further demonstrate that complex I activity is altered with disease state presenting high specificity and sensitivity.…”
mentioning
confidence: 99%